Extração do corante reactive blue 19 utilizando tensoativo não iônico - Melo, Ricardo Paulo Fonseca (2012)
The generation of effluent from the finishing process in textile industry is a serious environmental problem and turned into an object of study in several scientific papers. Contamination with dyes and the presences of substances that are toxic to the environment characterize this difficult treatment effluent. Several processes have already been evaluated to remove and even degrade such pollutants are examples: coagulation-flocculation, biological treatment and advanced oxidative processes, but not yet sufficient to enable the recovery of dye or at least of the recovery agent. An alternative to this problem is the cloud point extraction that involves the application of nonionic surfactants at temperatures above the cloud point, making the water a weak solvent to the surfactant, providing the agglomeration of those molecules around the dyes molecules by affinity with the organic phase. After that, the formation of two phases occurred: the diluted one, poor in dye and surfactant, and the other one, coacervate, with higher concentrations of dye and surfactants than the other one. The later use of the coacervate as a dye and surfactant recycle shows the technical and economic viability of this process. In this paper, the cloud point extraction is used to remove the dye Reactive Blue from the water, using nonionic surfactant nonyl phenol with 9,5 etoxilations. The aim is to solubilize the dye molecules in surfactant, varying the concentration and temperature to study its effects. Evaluating the dye concentration in dilute phase after extraction, it is possible to analyze thermodynamic variables, build Langmuir isotherms, determine the behavior of the coacervate volume for a surfactant concentration and temperature, the distribution coefficient and the dye removal efficiency. The concentration of surfactant proved itself to be crucial to the success of the treatment. The results of removal efficiency reached values of 91,38%, 90,69%, 89,58%, 87,22% and 84,18% to temperatures of 65,0, 67,5, 70,0, 72,5 and 75,0°C, respectively, showing that the cloud point extraction is an efficient alternative for the treatment of wastewater containing Reactive Blue